Genetic basis of local adaptation in the cold-tolerant mangrove Kandelia obovata - Zou, Chuangchao; Wang, Yushuai; Zhou, Renchao; Tang, Tian (Frontiers in Plant Science, 2024)
Understanding the genetic basis of local adaption is crucial in the context of global climate change.Mangroves, as salt-tolerant trees and shrubs in the intertidal zone of tropical and subtropical coastlines, are particularly vulnerable to climate change. Kandelia obovata, the most cold-tolerant mangrove species, has undergone ecological speciation from its cold-intolerant counterpart, Kandelia candel, with geographic separation by the South China Sea. In this study, we conducted whole-genome re-sequencing of K. obovata populations along China's southeast coast, to elucidate the genetic basis responsible for mangrove local adaptation to climate. Our analysis revealed a strong population structure among the three K. obovata populations, with complex demographic histories involving population expansion, bottleneck, and gene flow. Genome-wide scans unveiled pronounced patterns of selective sweeps in highly differentiated regions among pairwise populations, with stronger signatures observed in the northern populations compared to the southern population. Additionally, significant genotype-environment associations for temperature-related variables were identified, while no associations were detected for precipitation. A set of 39 high-confidence candidate genes underlying local adaptation of K. obovata were identified, which are distinct from genes under selection detected by comparison between K. obovata and its cold-intolerant relative K. candel. These results significantly contribute to our understanding of the genetic underpinnings of local adaptation in K. obovata and provide valuable insights into the evolutionary processes shaping the genetic diversity of mangrove populations in response to climate change.